Interstitial pneumonitis associated with pegylated interferon-alpha 2a and ribavirin for chronic hepatitis C infection: a case report - ÖZEN ALAHDAB, YEŞİM (My University, 2009)
Interstitial pneumonitis is a rare but potentially fatal side effect occurring from 2 weeks to 16 weeks after the initiation of treatment with pegylated interferon alpha and ribavirin for chronic hepatitis C.Herein, we present a 68-year-old man with chronic hepatitis C virus infection who developed interstitial pneumonitis association with pegylated interferon after 36 weeks initiation of pegylated interferon-alpha and ribavirin therapy. He did not recover after discontinuation of pegylated interferon/ribavirin and improved by steroid therapy.